Risk Analysis of 222Rn Gas Received from East Anatolian Fault Zone in Turkey - Yilmaz, Mucahit; Kulahci, Fatih (Amer Inst Physics, 2016)
In this study, risk analysis and probability distribution methodologies are applied for Rn-222 gas data received from Surgu (Malatya) station located on East Anatolian Fault Zone (EAFZ). Rn-222 data are recorded between 21.02.2007 and 06.06.2010 dates. For study are used total 1151 Rn-222 data. Changes in concentration of Rn-222 are modeled as statistically.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE